2022
DOI: 10.1021/acsami.2c08649
|View full text |Cite
|
Sign up to set email alerts
|

High Heat Resistance of the Structural Coloration of Colloidal Arrays with Inorganic Black Additives

Abstract: Structurally colored materials consisting of arrays of submicrometer-sized particles have drawn a great deal of attention because of their advantages, including low cost, low impact on human health as well as the environment, and resistance to fading. However, their low thermal stability is considered to be a critical issue for their practical use as colorants. Black-colored substances that can absorb the white color are added to colloidal array-type structurally colored materials to enhance their chromaticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…A logical step to avoid this lower stability would be the use of broadband absorbers of oxides which could stand higher temperatures. This was indeed recently demonstrated by Yamanaka et al [90] who showed stable structurally colored samples up to a temperature of 900 °C in air.…”
Section: Sustainabilitysupporting
confidence: 70%
“…A logical step to avoid this lower stability would be the use of broadband absorbers of oxides which could stand higher temperatures. This was indeed recently demonstrated by Yamanaka et al [90] who showed stable structurally colored samples up to a temperature of 900 °C in air.…”
Section: Sustainabilitysupporting
confidence: 70%
“…It can be found in Figure that the reflectance spectra changed little after heating in the air at 600 °C for 144 h; the α̅ solar and ε̅ IR were almost constant at 0.817 and 0.098, respectively. These results indicated that SSAs prepared by high-temperature in situ oxidation had excellent thermal stability at 600 °C, which can be attributed to the Cr 2 O 3 with outstanding thermal stability. …”
Section: Resultsmentioning
confidence: 84%
“…Considering the coloring mechanism of conventional structurally colored materials, one would not typically think of using structural color to develop transparent, deformable elastomers that exhibit a particular hue. On the other hand, in our previous studies, we have reported a number of systems in which the change in refractive index is isotropic due to the formation of short-range ordered aggregate structures of fine particles, resulting in little change in the hue of the structural color from any viewpoint. Even in such systems, if the distance of the short-range order changes with deformation of the material shape, the obtained hue will naturally change.…”
Section: Introductionmentioning
confidence: 82%
“…In this study, we have developed a transparent elastomer that exhibits an almost constant color regardless of elastomer deformation by utilizing the short-range ordered structure formed by fine particles. We have applied this system with short-range order in the refractive index to various systems since we first began studying it as a structurally colored material with little angular dependence. In the present study, we found that composite silica particles with uniform particle sizes, when combined with a cross-linked poly­(2-methoxyethyl acrylate) (PMEA), a widely used biocompatible material, result in a transparent structurally colored composite elastomer whose hue hardly changes with elongation of the composite elastomer. The composite elastomer was also found to have high mechanical toughness due to the introduction of fine particles.…”
Section: Introductionmentioning
confidence: 99%